การสร้างแบรนด์ภูมิภาคเชิงวัฒนธรรมเพื่อสามจังหวัดชายแดนภาคใต้ (ปัตตานี-ยะลา – นราธิวาส): เอกสารเชิงหลักการ - รักษาเกียรติ ชนกมณฐ์; สวัสดี ยอดขวัญ (วารสารวิจัยและนวัตกรรมการอาชีวศึกษา, 2023)
The purpose of this paper is to propose a cultural regional branding concept for the promotion of the creative economy in the three southern border provinces of Pattani, Yala, and Narathiwat. The concept is based on the factors of the creative economy and cultural industry, including six dimensions: (1) state dimension, (2) physical environment dimension, (3) infrastructure dimension, (4) people and society dimension, (5) activity and interesting dimension, and dimensions of economic and educational opportunities. The paper aims to provide guidelines and activities for cultural region branding, and to offer theoretical suggestions on cultural regional brand models that will add value to the economy and society, thereby improving the quality of life in the region. The proposed cultural regional branding concept is expected to contribute to the development of the creative economy in the three southern border provinces.